2011
DOI: 10.1002/chem.201102078
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Novel Fluorinated Ethanolamines

Abstract: The preparation of novel fluorinated allylamines and their use as key fragments for the stereoselective synthesis of hydroxyethyl secondary amine (HEA)-type peptidomimetics is described. Our strategy employs chiral sulfinyl imines as synthesis intermediates, by treatment of hemiaminal precursors with two equivalents of vinylmagnesium bromide. The subsequent oxidation of the allylic amines to the corresponding epoxides was achieved by treatment with methyl(trifluoromethyl)dioxirane. Finally, epoxide ring openin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…HEAs. The standard procedures for ring opening of the epoxide, 1 have been optimized that led to regioselective HEA analogs identified as scaffolds potent against malaria parasite [28][29][30] , plasmepsin inhibitors [31][32][33] , HIV inhibitors [34][35] etc.As a part of our ongoing research interest towards the search of new HEA scaffolds, synthesis of these analogs based on epoxide 1 was attempted following the standard conventional synthetic routes. Initially, ring opening reaction of epoxide 1 (1.0 mmol), with ptoluidine, 2a (1.0 mmol) in iso-propanol (50 mL) was carried out for 12 hours at 80 o C as reported in the literature [36] however, thin layer chromatography (TLC) did not indicate any product formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HEAs. The standard procedures for ring opening of the epoxide, 1 have been optimized that led to regioselective HEA analogs identified as scaffolds potent against malaria parasite [28][29][30] , plasmepsin inhibitors [31][32][33] , HIV inhibitors [34][35] etc.As a part of our ongoing research interest towards the search of new HEA scaffolds, synthesis of these analogs based on epoxide 1 was attempted following the standard conventional synthetic routes. Initially, ring opening reaction of epoxide 1 (1.0 mmol), with ptoluidine, 2a (1.0 mmol) in iso-propanol (50 mL) was carried out for 12 hours at 80 o C as reported in the literature [36] however, thin layer chromatography (TLC) did not indicate any product formation.…”
Section: Resultsmentioning
confidence: 99%
“…6-311G(d, p) level of theory. To simulate the solvate complexes, preliminarily the MOPS [32][33][34] algorithm was used, which search for the optimal geometry of a complex along all modes of translational, vibrational, and rotational movement in the combined force field MM3/MERA with a continual account the solvent influence according to the MERA model. Energies, geometrical, surface and charge characteristics were calculated within MERA model.…”
Section: Computationalmentioning
confidence: 99%
“…Inspired from the work by Elan and Pfizer [71], Fustero et al [72] synthesized fluorinated ethanolamines (Figure 3A) to analyze the essential fragments for the stereo-selective synthesis of hydroethyl secondary amine (HEA). They substituted phenyldifluoromethyl at the α-carbon of the HEA and explored the chemical space of the inhibitor by replacing hydrogen atoms at the benzylic position by fluorine atoms for enhancing the pharmacological profile of the series [44,73,74].…”
Section: The Role Of Fluorine-containing Compounds In the Modulation mentioning
confidence: 99%
“…The biological evaluation of these derivatives disclosed a notable BACE1 inhibitor activity. Docking studies showed the potential of fluorine atoms in influencing the potency of the inhibitors [72]. In 2015, Lilly's LY-2886721 [75] (Figure 3B) was the first 1,3-thiazine based BACE1 inhibitor advancing to a phase 2 trial.…”
Section: The Role Of Fluorine-containing Compounds In the Modulation mentioning
confidence: 99%
“…On the other hand, the characteristic bifunctional unit can undergo a wide range of chemical transformations, thus making allylamines versatile building blocks in organic synthesis [1]. Chiral allylamines, in particular, are valuable intermediates for the synthesis of a variety of chiral, enantiomerically-pure bioactive compounds [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%